Peran COVID-19 dalam Memoderasi Faktor Makroekonomi Terhadap Stock Return - Tony Chandra; Candy Chua (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2022)
The purpose of this study is not only focus on how macroeconomic factors can influence stock return, but also to determine how macroeconomic factors can influence stock return if associated with COVID-19. The paper uses secondary data with research methods quantitatively with type of causal comparative. The regression method used is panel data. This study uses companies that listed in the IDX High Dividend 20 as a sample by using purposive sampling method and resulted in total of 28 companies as samples. The result of this study found that exchange rate, interest rate, and dummy variable positively significantly influenced stock return. Additionally, it was also found out that inflation influenced stock return negatively and significantly. While the moderating test resulted in COVID-19 strengthening the influence of exchange rate, GDP, and money supply towards stock return. COVID-19 is also found to be weakening the influence of gold price towards stock return.